Climate Refugees. - Collectief, Argos; Jouzel, Jean; Reeves, Hubert (Singapore : Mitt Press, 2010)
Chomette, Guy-Pierre ; Collanges, Guillaume ; David, Hélène ; Daycard-Heid, Sébastien ; Derigny, Jérômine ; Faimali, Cédric ; Garnier, Donatien ; de Frahan, Eléonore henry ; Raux, Aude ; Weyl, Laurent ; Windenberger, Jacques
effect van klimaatsverandering op de mens, migratie, klimaatvluchtelingen
boek
Keywords: Collectif Argos